2019
DOI: 10.23860/jmle-2019-11-2-10
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Support: Using eCoaching to Increase Preservice Teachers’ Confidence to Teach

Abstract: The role of teacher education preparation programs is to equip preservice teachers (PSTs) with the knowledge and skills to support the development of all students. To do this, university faculty must establish and monitor PSTs' progress toward quality standards for teaching. eCoaching is a professional learning strategy that provides real-time feedback to PSTs during instruction. In this article, the authors present an overview of eCoaching logistics, a description of eCoaching in action, and perceived impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Researchers found that playing the game once reduced the player's perception of the reliability of false or misleading content by an average of 21% (Roozenbeek and van der Linden, 2019 [56]). The methodological shortcomings of this first study were addressed in a subsequent study and the significant impact of the game has since been confirmed and contrasted with a control group (Basol, Roozenbeek and Van der Linden, 2020 [61]) The game has now been translated into 15 languages.…”
Section: Box 15 Example Of An Inoculation Interventionmentioning
confidence: 95%
“…Researchers found that playing the game once reduced the player's perception of the reliability of false or misleading content by an average of 21% (Roozenbeek and van der Linden, 2019 [56]). The methodological shortcomings of this first study were addressed in a subsequent study and the significant impact of the game has since been confirmed and contrasted with a control group (Basol, Roozenbeek and Van der Linden, 2020 [61]) The game has now been translated into 15 languages.…”
Section: Box 15 Example Of An Inoculation Interventionmentioning
confidence: 95%